Towards large scale microwave treatment of ores: Part 2 - Metallurgical testing - Batchelor, A.R.; Buttress, A.J.; Jones, D.A.; Katrib, J.; Way, D.; Chenje, T.; Stoll, D.; Dodds, Chris; Kingman, S.W. (Elsevier, 2017)
A pilot scale microwave treatment system capable of treating 10-150t/h of material at 10-200kW was designed, constructed and commissioned in order to understand the engineering challenges of microwave-induced fracture of ores at scale and generate large metallurgical test samples of material treated at approximately 0.3-3kWh/t. It was demonstrated that exposing more of the ore to a region of high power density by improving treatment homogeneity with two single mode applicators in series yielded equivalent or better metallurgical performance with up to half the power and one third the energy requirement of that used with a single applicator. Comminution testing indicated that A*b values may be reduced by up to 7-14% and that the Bond Ball Mill Work Index may be reduced by up to 3-9% depending on the ore type under investigation. Liberation analysis of the microwave-treated ore indicated that equivalent liberation may be achievable for a grind size approximately 40-70µm coarser than untreated ore, which is in agreement with laboratory scale investigations reported in the literature at similar or higher doses. Flow sheet simulations further indicated that reduced ore competency following microwave treatment could potentially yield up to a 9% reduction in specific comminution energy (ECS) at a nominal plant grind of P₈₀190µm, or up to 24% reduction at a grind of P₈₀290µm, for a microwave energy input of 0.7-1.3kWh/t. Throughput could also be increased by up to approximately 30% depending on grind size, ore type and equipment constraints. To date, approximately 900t of material has been processed through the pilot plant, approximately 300t of which was under microwave power. Metallurgical testing has demonstrated that comminution and liberation benefits are achievable at doses lower than that previously reported in the literature, which allow high throughputs to be sustained with low installed power requirements providing a pathway to further scale-up of microwave treatment of ores.